2021
DOI: 10.1002/zamm.202100194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of entropy optimized Darcy‐Forchheimer flow in MnZnFe2O4 and NiZnFe2O4 hybrid nanofluid towards a curved surface

Abstract: The theme of this article is to scrutinize the entropy analysis for Darcy-Forchheimer flow of hybrid nanoliquid towards a stretched curved surface. Manganese and nickel (𝑀𝑛𝑍𝑛𝐹𝑒 2 𝑂 4 and 𝑁𝑖𝑍𝑛𝐹𝑒 2 𝑂 4 ) zinc ferrites are taken as nanoparticles. Here engine oil (𝐢 8 𝐻 18 ) is used as base liquid. Dissipation and radiation effects in energy equation are incorporated. The basic modeling of entropy analysis is developed through second law of thermodynamics. The governing nonlinear partial system (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The dimensionless form of the governing equations is presented in Equations ( 13)-( 16), satisfying the boundary conditions (17)(18). Due to its extremely complicated nature, this system cannot be treated via an exact solution approach.…”
Section: Numerical Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensionless form of the governing equations is presented in Equations ( 13)-( 16), satisfying the boundary conditions (17)(18). Due to its extremely complicated nature, this system cannot be treated via an exact solution approach.…”
Section: Numerical Computationsmentioning
confidence: 99%
“…Li et al [16] explored the slip onset for optimized nanofluid Jeffrey nanofluid flow numerically. Shah et al [17] reported the optimized production of NiZnFe 2 O 4 and MnZnFe 2 O 4 nanoparticles on curved surfaces. Micropolar nanofluid following pulsating motion in view of entropy generation applications was predicted by Rajkumar et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Alsharif et al [28] enhanced a micro-pump performance with help of second grade hybrid nanofluid with copper and titanium nanoparticles. Shah et al [29] optimized entropy in flow of a hybrid nanofluid on a curved surface. Alhowaity et al [30] studied flow of a hybrid nanofluid passing over a moving sheet with non-Fourier energy transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 14 , 15 ], the three-dimensional flow patterns with various effects and the addition of nanoparticles are investigated. Faqir shah et al [ 16 ] investigated the influence of entropy for hybrid nanofluid flow towards a curvy surface. Khalid Abdulkhaliq et al [ 17 ] examined the enhancement of heat transfer for slip flow of single and multi-walled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%